Scholars at war : Australasian social scientists, 1939-1945 - Gray, Geoffrey (Geoffrey G.); Munro, Doug; Winter, Christine (ANU E Press, 2012)
Examines the effect World War II had of the careers of Australasian social scientists. It links a group of scholars through geography, transnational, national and personal scholarly networks, and shared intellectual traditions, explores their use and contextualizes their experiences and contributions within wider examinations of the role of intellectuals in war.